Local Wisdom Integration in Islamic Education: Empowering Professionalism of Future Elementary School Educators - Muhammad Chamdani; Kartika Chrysti Suryandari; Murwani Dewi Wijayanti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the religious character and independence of elementary school teacher candidates through Project Based Learning (PjBL) and the effect of the PjBL model on religious character and independence. This research is a combination research (Mixed Methods). The combined method design model used in this research is a sequential exploratory design. The subjects in this study totaled 120 elementary school teacher candidates in semester 6 who were joined in three classes. The first stage is to use a qualitative approach using data collection techniques through observation, interviews, and documentation through project-based learning. Test the validity of the data using triangulation techniques. The data analysis technique for the Miles, Huberman, and Saldana model consists of three stages: data condensation, data display, and conclusions. The next stage is a quantitative study using a quasi-experimental type with a nonequivalent control group design. The sampling technique used was simple random sampling, so two classes were selected as the experimental class and one class as the control class. Data collection techniques using a questionnaire. The data analysis technique uses a statistical test, the Mann Withney-U test. The results of the analysis show that: 1) the project-based learning model can be used to strengthen the religious character and independence of prospective elementary school teachers as an effort to foster professionalism; 2) Project-based learning has a significant effect on the religious character and independence of prospective elementary school teachers with respective significance values of 0.002 and 0.003 meaning less than 0.05; 3) Religious character in terms of gender shows that women have a higher religious character than men; 4) Independence in terms of gender shows that men have higher independence than women